Effect of Adding Different Active Substances on Inhibition Zone Diameter and Microstructural Properties of Composite Bioplastics - Nelsy Dian Permatasari; Jatmiko Eko Witoyo; Donor Utomo M. Susilo; Ayu Rahayu Saraswati; Masruri; Sudarminto Setyo Yuwono; Simon Bambang Widjanarko (Jurnal Pangan dan Agroindustri)
Abstract